100 Effect of ruminally protected arginine and lysine supplementation on serum amino acids, performance and carcass traits of feedlot steers. (7th December 2018) - Schoonmaker, J; Rodrigues, L; Teixeira, P; Pukrop, J; Kim, Y; Tekippe, J
Abstract: Supplemental lysine (LYS) and arginine (ARG) have the potential to increase performance and carcass quality. Thus, we blocked 120 steers (322 ± 4.8 kg initial BW) by BW and randomly allocated them to 4 treatments arranged as a 2x2 factorial to determine the effect of ruminally protected LYS (0 or 40 g of 25% metabolizable LYS/d) or ARG (0 or 63 g of 16% metabolizable ARG/d) on blood metabolites, performance and carcass composition of feedlot steers. The basal diet contained (DM basis) 52% rolled corn, 22% DDGS, 20% corn silage and 6% supplement and supplied 93 and 86% of the steers LYS and ARG requirement, respectively. Protected LYS and ARG were top-dressed daily and increased dietary LYS and ARG to 113 and 105% of steers requirement, respectively. Steers were implanted with Synovex-ONE Feedlot at feedlot entry and were fed 300 mg of Optaflexx daily during the last 42 d. Steers were slaughtered at a common BW (622 ± 5.5kg). Data were analyzed using the MIXED procedure of SAS. Supplemental LYS or ARG did not impact total essential amino acid content in blood (P ≥ 0.15) and they did not affect BW, ADG, or DMI (P ≥ 0.14). Lysine decreased PUN (P = 0.03) and increased gain:feed (P = 0.03) during the first 87 d. Lysine increased (P = 0.01) L. dorsi area, decreased (P ≤ 0.01) fat thickness and yield grade, and increased (P ≤ 0.01) N and ash in L. dorsi steaks. Arginine tended to increase the proportion of Choice grade carcasses (P = 0.09) but did not impact lipid content of L. dorsi steaks (P = 0.89). In conclusion, supplemental LYS and ARG may not improve performance, but supplemental lysine can increase carcass leanness and arginine may improve marbling.